Kim and Kip in the Mirror of Mimicry: A Postcolonial Study - Islam, Dr. MD Rakibul; Hasan, DR. Nazia (The Grove - Working Papers on English Studies, 2020)
The research paper aims to give an accurate account of how Kirpal Singh/Kip in The English Patient by Michael Ondaatje copies the socio-cultural and linguistic norms of the Europeans (colonizers) unlike Kipling’s Kim who emulates the Eastern people (colonized) and their culture. They are examples of going through a long drawn process of growing up, looking into the mirror of mimicry. Kip joins the English army as a grown up, learns the need to show affinity to the new culture by way of imitation, adopting their ways to weave a comfort zone. Being different could be an assaulting fact for both sides, Kip is quick to realize that. But his childish view of looking down upon his native culture is the irony of mimicry. It wipes out the original being to rewrite a new identity. Kip leaves the small community sprouted accidentally in the Italian monastery, showing traces of a stricken conscience. Kim, by the virtue of living in close company of Indians, adopts their habits and manners without any qualm, in a most unconscious manner. He never worries to look or sound his original self which he has not experienced for long. Thus, a kind of reverse mimicry is his fate and character when we look at him as an outsider living as an Indian native. The ambivalence of their characters, presented by both, is an interesting aspect of mimicry. In the paper, we have used the views of postcolonial and cultural literary theorists on mimicry, deliberating upon how with the effect of both the processes, Kip and Kim, consciously or unconsciously, get their national identity peeled off, affixing new hybrid identity.